Sistema pré-fabricado para aplicação em construções provisórias de canteiros de obras - Knöner, Nery (2014)
The use of prefabricated elements has become increasing in Brazil, This paper describes the study and the procedures for construction and erection of a building system works on a pavement. Within the concept of technological innovation seeks to show a project in precast concrete that can be applied in facilities construction sites. Enables to meet the market demand for building construction sites in accordance with the requirements of the NR18 and ABNT (NB1367/NBR 12284, 1991), where all the actions of the production of construction happening and where the facilities are usually temporary and precarious. The system proposed solutions such as fast assembly, elimination of waste, and low cost, besides being a constructive process that can be reused in another bed, starting process without any loss of parts that compose it. Attaches itself to the system with one of the solutions that meets the needs of the construction industry in which it is possible to build construction sites, providing the employee satisfactory experiences in the area of enabling a modular installation adapting to the needs and administrative for the proper performance of the employee.